Investment Behavior in Digital Economy Era: Study From Universitas Terbuka’s Student - Ni Made Ayu Krisna Cahyadi; Suci Rahmawati Prima; Rini Febrianti; Sariwon Sariwon (Eqien - Jurnal Ekonomi dan Bisnis, 2026)
The aim of this study is to analyze the impact of financial literacy, investment motivation, risk perception, information technology, accessibility, trust, and lifestyle on the investment behavior of students in Faculty of Economics and Business, Universitas Terbuka. This study is quantitative research with primary data and uses multivariate analysis techniques. The results show that financial literacy, investment motivation, information technology, and trust have positive and significant effect on investment behavior. Meanwhile, risk perception, accessibility, and lifestyle have insignificant impact on investment behavior. This is because students make investments not based on risk perception and ease of accessibility, but rather based on assumptions about the future economy. Lifestyle does not affect their investment behavior because majority of students are proritizing their daily needs.